"No One is Illegal" As a Reverse Discourse Against Deportability. Issue 3 (3rd July 2022) - Seppälä, Tiina
ABSTRACT: After 2015, state authorities in many European countries actively stigmatised asylum-seekers and paperless, framing them as "illegal". In Finland, this illegality discourse was countered by resistant non-citizen and citizen subjects at multiple levels. This article examines the ways in which the arguments presented in the "No one is illegal" campaign can be considered to constitute a reverse discourse in a Foucauldian sense, and how it operates in the context of deportability which maintains structural inequality and racialised hierarchies based on the logic of political exclusion/inclusion embedded in state-centric sovereignty. It demonstrates how the state's illegality discourse contributed to a strong advance of social controls but enabled the formation of a reverse discourse that helped promote non-citizens' legal and political demands. While operating within the legal–illegal binary under which non-citizens were "disqualified" by the state, simultaneously, the reverse discourse strategically challenged it by utilising shared humanity as a common category.